2008
DOI: 10.1162/rest.90.4.599
|View full text |Cite
|
Sign up to set email alerts
|

Market Distortions When Agents Are Better Informed: The Value of Information in Real Estate Transactions

Abstract: Agents are often better informed than the clients who hire them and may exploit this informational advantage. Real estate agents have an incentive to convince clients to sell their houses too cheaply and too quickly. We test these predictions by comparing home sales in which real estate agents are hired to when an agent sells his own home. Consistent with the theory, we find homes owned by real estate agents sell for 3.7% more than other houses and stay on the market 9.5 days longer, controlling for observable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

34
350
3
4

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 492 publications
(391 citation statements)
references
References 25 publications
34
350
3
4
Order By: Relevance
“…Many literature have proven that Information asymmetry seriously exists in real estate markets (Cooper, et al 2000;Cutts and Order 2005;Firoozi et al 2006;Garmaise and Moskowitz 2004;Green 2008;Levitt and Syverson 2008;Rutherford et al 2007;Wong et al 2012). The asymmetry of information with respect to property prices comes from two sources.…”
Section: Financial Economics and Home Biasmentioning
confidence: 99%
“…Many literature have proven that Information asymmetry seriously exists in real estate markets (Cooper, et al 2000;Cutts and Order 2005;Firoozi et al 2006;Garmaise and Moskowitz 2004;Green 2008;Levitt and Syverson 2008;Rutherford et al 2007;Wong et al 2012). The asymmetry of information with respect to property prices comes from two sources.…”
Section: Financial Economics and Home Biasmentioning
confidence: 99%
“…In our model it is sufficient to receive exactly one offer to sell the house; in this case, on [0,t], P{N t ≥1} =1 -P{N t =0}=1 -e -λt , with 1/λ being the expected time for an offer to arrive. In real-world applications, we would set the arrival rate accordingly, for example, Levitt and Syverson (2008) indicate, for their local data, a mean time on the market of 111 days, for which we would have λ=0.009009.…”
Section: The Poisson Pricing Modelmentioning
confidence: 99%
“…This simple logic, however, is flawed. As Levitt and Syverson (2008) point out, there are a number of costs to the selling agent that increase over time, such as hosting open houses and placing advertisements. Since the agent receives only a small fraction of the selling price, a marginal increase in the price is perhaps not worth the extra effort and therefore a selling agent will have incentive to sell the house quickly, and for less money than the house might eventually bring.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that real estate markets are not always efficient. For example, Levitt and Syverson (2008); Miceli (1992) and Turnbull (1996) show that the existence of asymmetric information between home sellers and real estate agents leads to lower prices and more rapid sales when agents represent home sellers compared to when the agents sell their own homes. Clayton (1998);Crockett (1982) and Goolsby and Childs (1988) finds strong evidence against efficient markets in the condominium market in Vancouver.…”
Section: Introductionmentioning
confidence: 99%